Enhancing Students' Reading Comprehension of Intrinsic Story Elements through the Implementation of the Reading Thinking Activity (DRTA) Model Assisted by Flash Cards - Setyawati, Indah; Winarni, Retno; Yulisetiani, Septi (International Journal of Elementary Education, 2025)
Understanding the intrinsic elements of a story remains a challenge because conventional methods do not train students' critical thinking skills while reading. This study aims to analyze the effectiveness of the Directed Reading Thinking Activity (DRTA) model assisted by flash cards in enhancing students’ understanding of intrinsic story elements. The research employed a quasi-experimental method with a posttest-only control group design. The participants consisted of 64 students, divided into an experimental group of 32 students and a control group of 32 students, selected through cluster random sampling. Data were collected using a multiple-choice test measuring comprehension of story elements, including theme, characters, characterization, plot, setting, point of view, moral message, and language style. Data analysis involved descriptive statistics and an independent t-test. The findings revealed that the experimental group taught using the DRTA model with flash cards achieved higher post-test scores in the good category, while the control group taught through conventional methods remained in the fair category. The independent t-test confirmed a significant difference between the two groups. These results indicate that the DRTA model assisted by flash cards is effective in improving students’ reading comprehension of intrinsic story elements. The implication suggests that this model should be integrated into reading instruction to promote interactive, meaningful learning experiences and foster students’ critical thinking skills.